Patient perception on precipitating or aggravating factors for acne (Bangladesh Medical Journal, 2016)
Acne is a chronic inflammatory disease of the pilosebaceous glands which is an aesthetically unpleasant and embarrassing condition. Certain factors can precipitate or aggravate this condition. This study was done to identify factors believed by the patients that can precipitate or aggravate acne in our population. One hundred (100) patients with acne attending the Dermatology & Venereology outpatient Department of Bangabandhu Sheikh Mujib Medical University, Dhaka, from April 2014 to September 2014 were enrolled for the study. Patients were enquired about factors which aggravated or precipitated their acne by using a structured questionnaire and recorded for statistical analysis. Female patients (65%) and students (50%) suffered more from acne. Younger patients were more affected by the condition (56%). Use of topical steroid 32%, exposure to sunlight 23%, cosmetics 24%, stressful events, food 14%, skin pricking 16%, premenstrual period and dry weather 7% were found to be responsible for acne aggravation in those participants. Acne is more predominant in female patients and in younger age group who are more concerned with their cosmetic disfigurement. Prevention can be a good option if we can meticulously identify the aggravating factors.Bangladesh Med J. 2016 Jan; 45 (1): 31-35